2022
DOI: 10.2147/ijgm.s381404
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β and Interleukin-10 Profiles and Ratio in Serum of COVID-19 Patients and Correlation with COVID-19 Severity: A Time Series Study

Abstract: Background: Coronavirus disease-19 (COVID-19) can, in severe cases, lead to cytokine-release syndrome owing to an excessive immune response. The release of different cytokines aggravates disease severity. IL-1β is a pro-inflammatory cytokine, while IL-10 is an anti-inflammatory cytokine, and both are involved in the human immune response to infection. This study aimed to determine whether serum levels of IL-1β and IL-10 and the ratio of the two over time in patients with COVID-19 could facilitate early identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Although IL-1β induction is important to induce innate and adaptive immunity, unrestrained expression of IL-1β leads to severe inflammation in different diseases (Carta et al, 2017 ; Hoffman and Wanderer, 2010 ; Kaneko et al, 2019 ; Potere et al, 2022 ). Several studies suggest that IL-1β production is an important factor in inflammatory responses during COVID-19 (Del Valle et al, 2020 ; Makaremi et al, 2022 ; Potere et al, 2022 ; Yudhawati Sakina and Fitriah, 2022 ) but mechanisms that control IL-1β production or type-I IFN responses upon SARS-CoV-2 infection remain unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-1β induction is important to induce innate and adaptive immunity, unrestrained expression of IL-1β leads to severe inflammation in different diseases (Carta et al, 2017 ; Hoffman and Wanderer, 2010 ; Kaneko et al, 2019 ; Potere et al, 2022 ). Several studies suggest that IL-1β production is an important factor in inflammatory responses during COVID-19 (Del Valle et al, 2020 ; Makaremi et al, 2022 ; Potere et al, 2022 ; Yudhawati Sakina and Fitriah, 2022 ) but mechanisms that control IL-1β production or type-I IFN responses upon SARS-CoV-2 infection remain unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that COVID-19 infection showed an augmented inflammatory response, leading to the CS which is considered the main factor associated with organ failure and death [ 42 ]. Multiple proinflammatory cytokines were found elevated in the sera of COVID-10 patients, among which are IL-1β, IL-6, and TNF-α [ 43 ], which correlated with COVID-19 severity and mortality [ 44 , 45 ]. Also, systemic CRP and ferritin levels showed a significant positive association with severity and were independent predictors of survival in COVID-19 patients [ 46 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB causes dysregulation of oxidative phosphorylation which leads to the production of reactive oxygen species (ROS) that contributes to cytokine release and inflammation [48,49]. Clinical studies are presently ongoing to develop SARS-CoV-2 prognostication assays and associations with post-acute sequelae of COVID-19 (PASC) using the information from this pathway [50][51][52]. A recent study found that elevated IL-1β, IL-6, and TNF were associated with PASC.…”
Section: Interplay Between Malignancy Hypoxia and Sars-cov-2mentioning
confidence: 99%